1996
DOI: 10.1128/jvi.70.6.3741-3752.1996
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of viral replication correlate with outcome in simian immunodeficiency virus (SIV)-infected macaques: effect of prior immunization with a trivalent SIV vaccine in modified vaccinia virus Ankara

Abstract: The dynamics of plasma viremia were explored in a group of 12 simian immunodeficiency virus (SIV)infected rhesus macaques (Macaca mulatta) that had received prior immunization with either nonrecombinant or trivalent (gag-pol, env) SIV-recombinant vaccinia viruses. Three distinct patterns of viral replication observed during and following primary viremia accounted for significant differences in survival times. Highlevel primary plasma viremia with subsequently increasing viremia was associated with rapid progre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
96
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 292 publications
(109 citation statements)
references
References 45 publications
11
96
2
Order By: Relevance
“…In particular, baseline viral load shortly after acute infection (or 'viral load set point') has been shown to be highly prognostic for progression to AIDS [18][19][20] and is generally considered one of the best markers for disease progression in HIV seroconverters [21,22]. Similar results have been obtained in macaque challenge studies [23,24]; moreover, experimental interventions that reduced set point have been shown to delay disease progression [9,10,25]. Viral load has also been shown to be highly predictive of infectiousness [26] such that a vaccine's e ect on early viral load may also be a reasonable surrogate of VE I .…”
Section: Introductionsupporting
confidence: 65%
“…In particular, baseline viral load shortly after acute infection (or 'viral load set point') has been shown to be highly prognostic for progression to AIDS [18][19][20] and is generally considered one of the best markers for disease progression in HIV seroconverters [21,22]. Similar results have been obtained in macaque challenge studies [23,24]; moreover, experimental interventions that reduced set point have been shown to delay disease progression [9,10,25]. Viral load has also been shown to be highly predictive of infectiousness [26] such that a vaccine's e ect on early viral load may also be a reasonable surrogate of VE I .…”
Section: Introductionsupporting
confidence: 65%
“…Recombinant attenuated orthopoxviruses have also shown comparable immunogenicity to replication-competent vaccinia in numerous animal studies [38,[44][45][46]. Although most have focussed on T cell responses against the encoded transgenes, some have assessed antibody induction.…”
Section: Antibody Induction By Attenuated Poxviral Vectorsmentioning
confidence: 99%
“…One promising VACV vaccine candidate is based on the highly attenuated virus strain modified VACV Ankara (MVA) [14][15][16]. MVA has also been developed as a nonreplicating viral vector to construct experimental recombinant vaccines against various infectious diseases [17][18][19][20][21][22]. Immunizations with MVA in animal models proved highly efficacious when compared to conventional VACV vaccines, and elicited antigenspecific humoral and cellular immune responses [19,[23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%